Genetic and molecular analysis of the gypsy chromatin insulator of Drosophila. - Gdula, D A (1996)
Boundary or insulator elements set up independent territories of gene activity by establishing higher order domains of chromatin structure. The gypsy retrotransposon of Drosophila contains an insulator element that represses enhancer-promoter interactions and is responsible for the mutant phenotypes caused by insertion of this element. The gypsy insulator inhibits the interaction of promoter-distal enhancers with the transcription complex without affecting the functionality of promoter-proximal enhancers; in addition, these sequences can buffer a transgene from chromosomal position effects. Two proteins have been identified that bind gypsy insulator sequences and are responsible for their effects on transcription. The suppressor of Hairy-wing [su(Hw)] protein affects enhancer function both upstream and downstream of its binding site by causing a silencing effect similar to that of heterochromatin. The modifier of mdg4 [mod(mdg4)] protein interacts with su(Hw) to transform this bi-directional repression into the polar effect characteristic of insulators. These effects seem to be modulated by changes in chromatin structure.